Not All Daydreaming Is Equal: A Longitudinal Investigation of Social and General Daydreaming and Marital Relationship Quality - Kajimura, Shogo; Nozaki, Yuki; Goto, Takayuki; Smallwood, Jonathan (Frontiers in Psychology, 2022)
Preliminary evidence suggests that daydreaming about other people has adaptive value in daily social lives. To address this possibility, we examined whether daydreaming plays a role in maintaining close, stable relationships using a 1-year prospective longitudinal study. We found that individuals’ propensity to daydream about their marital partner is separate to general daydreaming. In contrast to general daydreaming, which was associated with lower subsequent relationship investment size (i.e., magnitude and importance of resources attached to a relationship) in the marital partner, partner-related social daydreaming led to a greater subsequent investment size. Additionally, attachment styles moderated these effects. The effect of daydreaming regarding investment size was found only in securely attached individuals. This research advances the emerging field of social daydreaming and highlights self-generated thought as a critical tool that can help people navigate the complex social world.